Novel Lyssavirus from a Miniopterus schreibersii bat in Spain (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In the frame of the Spanish Rabies Surveillance Program, a bat carcass was received on March 12th, 2012, in the Centro Nacional de Microbiología (National Center of Microbiology) (CNM). The bat was found in the city of Lleida, in July 2011, and it was taken to the Wildlife Care Center of Vallcalent (Lleida, Catalonia). The bat died soon after admission. Two different RT-PCR generic methods for the Lyssavirus genus (1,2) and two commercial rabies antisera for antigen detection were used for diagnosis. Brain smears were positive for both, FAT and RT-PCR, as well as the oropharingeal swab for RT-PCR. The bat was morphologically and molecularly identified as Miniopterus schreibersii (3). To determine the identity of the virus, a fragment of the nucleoprotein gene (N) was sequenced. Dataset representative of all Lyssaviruses, including the recently described IKOV, was used for the phylogenetic reconstruction. The topology obtained by Bayesian Inference (BI) showed a new virus related more to IKOV and WCBV than any other lyssavirus included in phylogroups I and II. These results suggest a new virus, named Lleida bat lyssavirus (LLEBV), taking in consideration the locality where the bat was found. In Europe, from 1977 to 2011, a total of 988 cases of bat rabies were reported; Eptesicus serotinus and E. isabellinus which account for more than 95% of the cases are considered the major natural reservoirs of EBLV-1. Several Myotis spp. are reservoirs for EBLV-2, BBLV, ARAV, and KHUV(4). In Spain, EBLV-1 has only been described in E. isabellinus (5). Interestingly, the lowest nucleotide identity shown by LLEBV was with EBLV-1. The LLEBV has been detected on M. schreibersii such as WCBV. Miniopterus genus presently belongs to the Vespertilionidae family as the other bat genera linked to lyssaviruses in Eurasia (Eptesicus, Myotis and Murina). However, recent molecular analyses have postulated the group as an independent monospecific Miniopteridae family (6). M. schreibersii is a migratory bat, widely distributed throughout Southern Europe and Eurasia. This bat specie gathers in caves in large numbers (thousands) for wintering, moving in spring to different and sometimes distant summer roosts for reproduction. Due to its migratory habits and typically large size of populations of this bat, it is quite probable that once an infectious agent is introduced, it may spread quickly within populations. The evolutionary relationships between the new LLEBV with WCBV and IKOV need to be clarified to determine whether they will form one or more phylogroups. Further analyses are in process to assess this question and to establish a probable potential role as a human pathogen. More studies must be done in order to evaluate ecological aspects of LLEBV circulation. Nidia Aréchiga Ceballos is post-doctoral fellow granted by the Consejo Nacional de Ciencia y Tecnología (CONACyT) Mexico. This research was financially supported by the project SAF 2009-09172 of the General Research Program of the Spanish Ministry of Science and Education.